2021
DOI: 10.3390/act10020023
|View full text |Cite
|
Sign up to set email alerts
|

Torque Characteristics Analysis of a Magnetorheological Brake with Double Brake Disc

Abstract: Magnetorheological (MR) brake is a sort of electromagnetic brake that uses the controllable output characteristics of MR fluid for braking. In this paper, an MR brake with a double brake disc was developed to improve the braking performance of conventional MR brakes. The effective damping gaps were increased from the traditional two sections to four sections by increasing the single brake disc of the conventional MR brake to a double brake disc. By reasonably arranging the non-magnetic sleeve inside the MR bra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…Various every day devices, such as shock absorbers [8,9], brakes [10,11], clutches [12], earthquake dampers [13,14], control valves [15,16], mounts [17][18][19], thermal energy transfers [20], biomedical applications [21], precision polishing [22], and sound propagation devices [23,24], are made possible due to the properties of these smart materials. Based on the studies above, it is evident that MRFs are mostly used in energy dissipating devices and not in an active energy actuating device due to its operational modes.…”
Section: Introductionmentioning
confidence: 99%
“…Various every day devices, such as shock absorbers [8,9], brakes [10,11], clutches [12], earthquake dampers [13,14], control valves [15,16], mounts [17][18][19], thermal energy transfers [20], biomedical applications [21], precision polishing [22], and sound propagation devices [23,24], are made possible due to the properties of these smart materials. Based on the studies above, it is evident that MRFs are mostly used in energy dissipating devices and not in an active energy actuating device due to its operational modes.…”
Section: Introductionmentioning
confidence: 99%
“…So far, a comprehensive approach to the problem of solving time-dependent coupled field phenomena in MR devices has not yet been the subject of research discussed in the open literature. It can be observed that in the research area subjected to the analysis of MR transducers, the field approach is applied only for selected phenomena (for example, electromagnetic), while simplified models of fluid dynamics or temperature fields are incorporated [ 9 , 17 , 20 , 24 , 34 ].…”
Section: Coupled Field Model Of Phenomena In Hemrfbmentioning
confidence: 99%
“…The results confirmed that the gap size significantly influences the braking performance. Hu et al (2021) and Shiao et al (2021) conducted a related study on multi-disc MRB, and the results indicated that the braking performance of the MRB can be improved by increasing the number of brake discs. In the follow-up research, Shiao and Kantipudi (2022) proposed an MRB which adopted dual disc-type construction to achieve high torque density.…”
Section: Introductionmentioning
confidence: 99%